Goal Orientation and the Presence of Competitors Influence Cycling Performance - Hibbert, Andrew W.; Billaut, François; Varley, Matthew C.; Polman, Remco C. J. (Frontiers in Psychology, 2018)
Introduction: The aim of this study was to investigate time-trial (TT) performance in the presence of one competitor and in a group with competitors of various abilities. Methods: In a randomized order, 24 participants performed a 5-km cycling TT individually (IND), with one similarly matched participant (1v1), and in a group of four participants (GRP). For the GRP session, two pairs of matched participants from the 1v1 session were used. Pairs were selected so that TT duration was considered either inferior (INF) or superior (SUP) compared to the other pair of participants. Results: Overall, TT duration (P = 0.86, ηp2 < 0.01) was not different between conditions, whilst heart rate (HR) was significantly greater in GRP compared to IND (P < 0.01, ηp2 = 0.16). For INF, a large effect size for both mean power (P = 0.07, ηp2 = 0.15) and HR (P = 0.05, ηp2 = 0.16), indicates greatest effort in GRP. Pacing behaviour was affected by competition but similar in 1v1 and GRP for SUP, whilst large effect sizes indicate an increased power output in the initial 750-m for INF in GRP. Additionally, for INF, there was a significant correlation with ego orientation for an increase in TT duration between the GRP session and both the IND (r = 0.43, P = 0.04) and 1v1 (r = 0.54, P = 0.01) sessions. Conclusion: For INF participants, intensity was increased when competing in GRP. Yet, the presence of the SUP competitors resulted in lesser performance improvements for ego oriented INF participants. These findings demonstrate that consideration should be given to the ability of competitors in a group setting to provide adequate motivation.